Hungarian Monitoring, 23 September 1988 . [Magyar rádiófigyelő], 1988. szeptember 23 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Shevardnadze's Washington schedule - Polish democratic party demands greater independence - Thatcher's west European trip - Lebanese domestic situation - Summary on Karabakh Domestic Affairs: - Péter Várkonyi travels to UN General Assembly in New York - President of EEC council arrives in Budapest - Former Recsk labor camp internees form association - "Home from home" three-day series of events to help Romanian refugees - Swedish experts study Gabčíkovo-Nagymaros plans and construction over two weeks - Popular Front committee: multi-party system would have stabilizing impact over long term - Csaba Hámori, first Young Communist League (KISZ) Central Committee secretary, at opening of Békésmegye youth days: trust in the new leadership is wearing thin - Plan to hold joint Budapest-Vienna World Exposition wins Swiss prize Economy: - Draft companies and tax laws - Hungarian-Soviet joint tourism company to start operations soon in Moscow Külpolitika: - Sevardnadze washingtoni programja - Nagyobb önállóságot követel a lengyel demokrata párt - Thatcher nyugat európai körútja - A libanoni belpolitikai helyzet - Karabahi összefoglaló Belpolitika: - Az ENSZ közgyűlésére New Yorkba utazott Várkonyi Péter - Budapestre érkezett az Európai Gazdasági Közösség tanácsának soros elnök - Szövetséget alakítottak az egykori recski internáltak - Otthontól - Hazáig címmel, háromnapos rendezvénysorozat kezdődött a romániai menekültek segítésére - Svéd szakértők tanulmányozták két héten át a bős-nagymarosi vízlépcső terveit, az építkezést - Hosszú távon stabilizáló lenne a többpárt-rendszer megjelenése, hangzott el a Népfront egyik szakbizottságában - Kezd megkopni az új vezetés iráni bizalom - Ezt Hámori Csaba a KISZ KB első titkára jelentette ki a békésmegyei ifjúsági napok megnyitóján - Budapest-Bécs svájci nívódíjat kapott a közös világkiállítás megrendezésének tervéért Gazdaság: - Társasági és adótörvény tervezet - Moszkvában hamarosan megkezdi működését a magyar-szovjet idegenforgalmi vegyesvállalat